A novel instrument for the prevention of condylar torque in bilateral sagittal ramus osteotomy when using bicortical screw fixation. Issue 3 (March 2022) - Van den Borre, C.; Van de Casteele, E.; Boeckx, P.; Nadjmi, N.
Abstract: When using the bilateral sagittal split osteotomy (BSSO) technique, rigid internal fixation (RIF) remains the standard method to accurately fix the distal and proximal osteotomy fragments. A concern with the use of RIF, especially with bicortical screws, is the increased risk of condylar torque and its functional consequences. This technical note introduces a new method for preventing torque of the mandibular condyles after BSSO, using a sagittal split space maintainer.